The influence of the boxing stance on performance in professional boxers - Sorokowski, Piotr; Sabiniewicz, Agnieszka; Wacewicz, Sławomir (Anthropological Review, 2014)
In boxing, athletes choose between two strategies: the orthodox stance characteristic of right handed competitors, or the southpaw stance characteristic of left-handers. Despite a conviction popular among the practitioners of this sport that fighting against a southpaw opponent constitutes a handicap, the effectiveness of the type of stance has so far not been examined. We extracted the statistics of the top twenty active male professionals boxing in each of the seventeen weight divisions. Out of the 340 boxers who composed our group, 75% used the orthodox stance and 25% were southpaw. Generally, we found that boxing stance had no effect on the percentage of 340 top professional boxers’ victories. However, both the southpaw and the orthodox athletes had a higher percentage of victories against orthodox boxers than against southpaws.